Localization, regulation and functions of neurotransmitters and neuromodulators in cervical sympathetic ganglia - Klimaschewski, Lars Peter; Kummer, Wolfgang; Heym, Christine (Microscopy research and technique, 1996)
Cervical sympathetic ganglia represent a suitable model for studying the establishment and plasticity of neurochemical organization in the nervous system since sympathetic postganglionic neurons: (1) express several neuromediators, i.e., short acting transmitters, neuropeptide modulators and radicals, in different combinations; (2) receive synaptic input from a limited number of morphologically and neurochemically well-defined neuron populations in the central and peripheral nervous systems (anterograde influence on phenotype); (3) can be classified morphologically and neurochemically by the target they innervate (retrograde influence on phenotype); (4) regenerate readily, making it possible to study changes in neuromediator content after axonal lesion and their possible influence on peripheral nerve regeneration; (5) can be maintained in vitro in order to investigate effects of soluble factors as well as of membrane bound molecules on neuromediator expression; and (6) are easily accessible. Acetylcholine and noradrenaline, as well as neuropeptides and the recently discovered radical, nitric oxide, are discussed with respect to their localization and possible functions in the mammalian superior cervical and cervicothoracic (stellate) paravertebral ganglia. Furthermore, mechanisms regulating transmitter synthesis in sympathetic neurons in vivo and in vitro, such as soluble factors, cell contact or electrical activity, are summarized, since modulation of transmitter synthesis, release and metabolism plays a key role in the neuronal response to environmental influences. © 1996 Wiley-Liss, Inc.